Morphological features and occurrence of degenerative characteristics in the hypopharyngeal glands of the paper wasp Polistes versicolor (Olivier) (Hymenoptera : Vespidae) - Britto, Fabio Barros; Caetano, Flavio Henrique (Elsevier B.V., 2006)
Different histochemical techniques were applied to examine the morphological features of the secretory cells of hypopharyngeal glands in the wasp Polistes versicolor. The results showed that most analyzed individuals present active glands with secretion stored in the cytoplasm. In some glands, morphological analyses revealed the presence of degenerative characteristics. Analyses of cellular integrity, however, did not detect dead cells. The results showed that, in P. versicolor, the development and regression of the hypopharyngeal glands were not age related, unlike glands of social bees. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: hypopharyngeal glands; salivary system; Polistes versicolor; wasps; Hymenoptera; cell death; histochemistry; histology